Regulation of cerebellar network development by granule cells and their molecules - Kim, Muwoong; Jun, Soyoung; Park, Heeyoun; Tanaka-Yamamoto, Keiko; Yamamoto, Yukio (Frontiers in Molecular Neuroscience, 2023)
The well-organized cerebellar structures and neuronal networks are likely crucial for their functions in motor coordination, motor learning, cognition and emotion. Such cerebellar structures and neuronal networks are formed during developmental periods through orchestrated mechanisms, which include not only cell-autonomous programs but also interactions between the same or different types of neurons. Cerebellar granule cells (GCs) are the most numerous neurons in the brain and are generated through intensive cell division of GC precursors (GCPs) during postnatal developmental periods. While GCs go through their own developmental processes of proliferation, differentiation, migration, and maturation, they also play a crucial role in cerebellar development. One of the best-characterized contributions is the enlargement and foliation of the cerebellum through massive proliferation of GCPs. In addition to this contribution, studies have shown that immature GCs and GCPs regulate multiple factors in the developing cerebellum, such as the development of other types of cerebellar neurons or the establishment of afferent innervations. These studies have often found impairments of cerebellar development in animals lacking expression of certain molecules in GCs, suggesting that the regulations are often mediated by molecules that are secreted from or present in GCs. Given the growing recognition of GCs as regulators of cerebellar development, this review will summarize our current understanding of cerebellar development regulated by GCs and molecules in GCs, based on accumulated studies and recent findings, and will discuss their potential further contributions.